Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Kebersihan Asrama - Alfiah Aulia Ilmiana; Ahmad Asrof Fitri; Sobirin Sobirin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Cleanliness issues remain a persistent challenge in Islamic boarding school dormitories, particularly regarding poor sanitation, limited cleaning personnel, low student participation, and a general lack of awareness among residents. This study aims to examine the roles of management and human resources (HR) in addressing these issues at Al-Musthafa Dormitory. Employing a descriptive qualitative approach, the research focuses on individual experiences to gain in-depth insights into the implementation of management and HR roles. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that dormitory management plays a strategic role in improving environmental hygiene through structured planning, organizing, directing, and controlling functions. Furthermore, HR at Al-Musthafa significantly contributes to the effectiveness of cleanliness policies by establishing clear rules and regulations and encouraging active student participation in organized hygiene programs.